Validation of a self‐administered olfactory and gustatory test for the remotely evaluation of COVID‐19 patients in home quarantine. Issue 7 (9th May 2020) - Vaira, Luigi Angelo; Salzano, Giovanni; Petrocelli, Marzia; Deiana, Giovanna; Salzano, Francesco Antonio; De Riu, Giacomo
Abstract: Background: Chemosensitive disorders are very frequent in the early stages of COVID‐19 and in paucisymptomatic cases. These patients are typically placed in home quarantine. This study has the aim of validating a new olfactory and gustatory objective evaluation test in these patients. Methods: Thirty‐three home‐quarantined COVID‐19 patients have undergone a self‐administered chemosensitive test the day before the control swab. On this occasion, the patients underwent operator‐administered already validated tests. The results were finally compared. Results: The differences between the results of the two tests were not significant for both the olfaction ( P  =.201) and the taste ( P  =.180). Conclusion: The olfactory and gustatory evaluation by self‐administered test can be considered a valid tool, fundamental for obtaining objective qualitative and quantitative data on the extent of chemosensitive disorders in home‐quarantined COVID‐19 patients.